2009
DOI: 10.7202/037683ar
|View full text |Cite
|
Sign up to set email alerts
|

When Idioti (Idiotic) Becomes “Fluffy”: Translation Students and the Avoidance of Target-language Cognates

Abstract: Cognate translation is neither a simple nor a straightforward matter. Given the risk that a word that appears to be a true cognate may actually be a false cognate, and given the sometimes fuzzy boundary between true and false cognates, translators and translation students have been shown to “play it safe” by casting around for noncognate translations for true cognates, rather than choose the obvious cognate translation. Here we ask whether translation students avoid cognate translations even when the target-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…Cognate equivalents were used similarly in ST and SI. In fact, there was no clear preference for cognate or non-cognate solutions in either task, which is not in line with the trend to avoid using cognates revealed, albeit in written translation, by Malkiel (2009). This result is also at variance with the findings by Shlesinger and Malkiel (2005) who revealed more cognates used in a more difficult mode -this might be partially due to different tasks used in that study (written translation and SI) and different participants (professional interpreters).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Cognate equivalents were used similarly in ST and SI. In fact, there was no clear preference for cognate or non-cognate solutions in either task, which is not in line with the trend to avoid using cognates revealed, albeit in written translation, by Malkiel (2009). This result is also at variance with the findings by Shlesinger and Malkiel (2005) who revealed more cognates used in a more difficult mode -this might be partially due to different tasks used in that study (written translation and SI) and different participants (professional interpreters).…”
Section: Discussioncontrasting
confidence: 75%
“…This means that due to form/meaning similarity, cognate equivalents are first activated and immediately selected from among other potential competitors. In the other study, Malkiel (2009) confirmed her hypothesis about translation trainees avoiding the use of cognates. Malkiel also found a negative correlation between cognate avoidance and mistranslation of homophones: trainees who were more sensitive to potential traps related to cognates were more successful in translating homophones.…”
Section: Lexical Interference -Cognates and Homographssupporting
confidence: 60%
See 1 more Smart Citation
“…The formulation of this hypothesis is additionally motivated by the final target versions of all participants: this instance of the noun ball was translated by Ball by five out of nine participants. Assuming this target hypothesis, the change of plan could be potentially explained through the wish to avoid cognates, which are more readily accessible than other synonyms but can result in non-idiomatic target language expressions (Malkiel, 2009b).…”
Section: Erhöte•i◄◄◄◄hte•e◄energiespeicherungmentioning
confidence: 99%
“…Many patterns that were once believed to be unique to translation are now being explored as potential effects of a much more encompassing bilingual language production (Halverson 2003(Halverson , 2013House 2008House , 2013Szymor 2018;De Sutter and Lefer 2020;Vandevoorde 2020). We want to continue this line of research by taking into consideration three possible socio-cognitive explanations, as identified by Kruger (2019), for the different onomasiological choices in translated and non-translated texts that are not restricted to translational behaviour alone, but are often used to explain usage patterns in (bilingual) language production in general, and thus have much more explanatory power: the complexity principle (Rohdenburg 1996), risk aversion (Pym 2015), and cognate exposure (Costa, Colomé, and Caramazza 2000;Malkiel 2009aMalkiel , 2009b. These three explanations are discussed in Section 2.…”
mentioning
confidence: 99%